Evaluating the substitutability of short-haul air transport by high-speed rail using a simulation-based approach. (September 2022) - Rajendran, Suchithra; Popfinger, Maximilian
Highlights: Air travel has the highest CO2 emission per passenger kilometer. Evaluated the substitutability of short-haul air transport by high-speed rail (HSR). Determined the extent to which current rail network can handle air passengers. Used discrete-event systems simulation approach for model development. Results indicate that current HSR system can only handle 25% additional customers. Abstract: Air transportation is reported to have the highest CO2 emission per passenger kilometer compared to other modes of travel. Although prior studies have analyzed the impact of high-speed rail (HSR) on the aviation sector, this study is one of the first to develop a simulation model to evaluate the current HSR system, and determine the extent to which the existing rail network can handle additional passengers, if short-haul airline customers were to avail of HSR service. This study also proposes recommendations for future HSR schedules and rail capacities, as well. A Define, Measure, Analyze, Design, and Verify (DMADV) approach is developed for (a) conceptualizing the problem, (b) collecting data from different sources, (c) developing the simulation model, and (d) evaluating the results and deriving managerial recommendations. For the purpose of illustrating the proposed approach, we discuss a case study considering the passenger travel between two major European cities, Munich and Paris. It can be observed that the current railway operations between Munich and Paris could only handle 25% additional customers. If 50%, 75% and 100% of current air customers were to switch to HSR, then it is recommended to operate one (evening), two (one afternoon and one evening), and three (two afternoon and one evening) additional trains, respectively. Furthermore, this study shows that a complete customer transition from air to rail could save 56.8% in CO2 emission.